Irritable mood and the Diagnostic and Statistical Manual of Mental Disorders - Safer Daniel J (BMC, 2009)
Abstract Background The terms 'irritable mood' and 'irritability' have been applied to describe and define a variety of different categories in the Diagnostic and Statistical Manual of Mental Disorders (DSM). More precise diagnostic terms and concepts are needed. Methods A concise critical historical review of DSM categories characterized by irritability, anger, and aggression is presented followed by recommendations. Results This analysis describes the broad ranging and imprecise use of the term irritability since the first DSM in 1952. A more age-appropriate and functional realignment of psychiatric categories linked to dysfunctional anger is suggested. Among other recommendations, this realignment would remove irritability as a problematic definer in the present DSM mood categories: expand oppositional defiant disorder to include adults; link the callous unemotional subtype of conduct disorder in adolescents to antisocial personality disorder; move intermittent explosive disorder to an appropriate category: and expand the term 'mood' to apply also to dysfunctional anger and anxiety. Conclusion The non-specific term 'irritability' commonly used in the DSM has had an adverse effect on diagnostic specificity and thereby on treatment. Dysfunctional anger is a major mood disorder which merits a more prominent and better defined representation in psychiatric nomenclature.